Explanatory Note On Anti Money Laundering (Amendment) Act 2003 - Abd Hamid Abd Murad (Universiti Sains Islam Malaysia, 2024)
This article discusses some of the changes brought about by the amendments of Anti Money Laundering (Amendments) Acts 2003. It examines whether the legal principles under this law are able to address the scandals which have emerged in recent years pertaining to auditors. It also investigates whether the legal principles under criminal law impose additional duties and obligations on auditors as opposed to those duties and obligations imposed under the company law. The study finally examines whether action can be brought against the auditors and the difficulties faced in doing so. These issues are extremely crucial because auditors profession is becoming a high-risk profession. This study suggests that the current legal framework under criminal law governing auditors must be reassessed in the wake of the scandals involving auditors both in the domestic and international forefront.